2021
DOI: 10.2196/32936
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Public Health Events on COVID-19 Vaccine Hesitancy on Chinese Social Media: National Infoveillance Study

Abstract: Background The ongoing COVID-19 pandemic has brought unprecedented challenges to every country worldwide. A call for global vaccination for COVID-19 plays a pivotal role in the fight against this virus. With the development of COVID-19 vaccines, public willingness to get vaccinated has become an important public health concern, considering the vaccine hesitancy observed worldwide. Social media is powerful in monitoring public attitudes and assess the dissemination, which would provide valuable inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 51 publications
1
17
1
Order By: Relevance
“…An important finding of this study was that greater vaccine-hesitant attitudes were found in men when compared to women. This is not consistent with findings in the literature where women were found to be more vaccine-hesitant than men [ 28 - 29 ]. However, this can be attributed to the findings from other studies that reported that women were more adherent to medical recommendations and are more cautious about their health [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…An important finding of this study was that greater vaccine-hesitant attitudes were found in men when compared to women. This is not consistent with findings in the literature where women were found to be more vaccine-hesitant than men [ 28 - 29 ]. However, this can be attributed to the findings from other studies that reported that women were more adherent to medical recommendations and are more cautious about their health [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…These results constitute a strong call for policy-makers to adjust vaccination policies rapidly in response to the public health events to promote massive vaccination via dynamic monitoring of public sentiment. 112 Finally, in this systematic review we also observed that data mining and natural language processing techniques proved to be very useful and beneficial in analyzing and understanding public perspectives regarding this critical public health issue and thereby providing meaningful and valuable insights. This is also in line with more emerging research in the literature that was not within the scope of this review, but nevertheless reiterating such notions.…”
Section: Discussionmentioning
confidence: 86%
“…The emotional score calculated by the method is between 0 and 1. The larger the value is, the more optimistic the news is (Zhang, Feng, et al, 2021).…”
Section: Research Methods and Data Sourcesmentioning
confidence: 99%